2010
DOI: 10.1016/j.elecom.2009.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Carbon ceramic nanoparticulate film electrode prepared from oppositely charged particles by layer-by-layer approach

Abstract: Carbon ceramic nanoparticulate film electrode was prepared of negatively charged sulfonated carbon nanoparticles and positively charged silicate submicrometre particles with appended imidazolium groups. They were immobilised on indium tin oxide surface by layer by layer method: alternative immersion into suspension of positive and negative particles. Film formation is confirmed by scanning electron microscopyafter larger number of immersion and withdrawal steps more material is deposited on the electrode subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Due to their imidazolium functional groups, this electrode acts as a reversible sponge for electroactive anions. These silicate particles can be used as a linker for immobilization of carbon nanoparticles with anionic functionalities using layer-by-layer procedure [315]. After further modification with laccase, this electrode exhibits bioelectrocatalytic dioxygen reduction [315].…”
Section: Electrodes Modified With Appended Ionic Liquidsmentioning
confidence: 99%
“…Due to their imidazolium functional groups, this electrode acts as a reversible sponge for electroactive anions. These silicate particles can be used as a linker for immobilization of carbon nanoparticles with anionic functionalities using layer-by-layer procedure [315]. After further modification with laccase, this electrode exhibits bioelectrocatalytic dioxygen reduction [315].…”
Section: Electrodes Modified With Appended Ionic Liquidsmentioning
confidence: 99%
“…It was also demonstrated that with LbL approach one can prepare conductive films combining negatively charged conductive CNPs and isolating functionalized silicate submicroparticles 36, 45, 46. This indicates that percolation paths of CNPs are formed instead of well defined separate layers of different types of particles, because of the dense coverage of silicate submicroparticles with oppositely charged CNPs (Fig.…”
Section: Immobilization Of Cnps At the Electrode Surfacementioning
confidence: 90%
“…The films of various types of carbon nanoparticles have also been applied as a platform for immobilizing bacteria 6365 6466 and enzymes as glucose oxidase (HRP) 39, 46, 66 21, 41, 48, 78, hydrogenase 42, ethanol dehydrogenase 49, horseradish peroxidase 48, 78. These bioanodes are capable for oxidation of such fuels as glucose 21, 28, 48, 78, hydrogen 42, acetate 66 or ethanol 49.…”
Section: Carbon Nanoparticles Modified Bioelectrocatalytic Electrodesmentioning
confidence: 99%
“…As previously reported in the literature, laccase can be immobilized on the surface of a CCE and successfully employed for amperometric determination of a variety of phenolic substrates [10] and also in the study of bioelectrocatalytic dioxygen reduction [11][12][13][14].…”
Section: Introductionmentioning
confidence: 97%